Pengaruh Program Kids Athletics terhadap Keterampilan Motorik Dasar Kelas V Sekolah Dasar - Pika Amelia Putri; Ricky Wibowo; Mukhlisin (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
A decline in fundamental motor skills among primary school-aged children is an issue that affects their ability to perform physical activities optimally. This study aimed to determine the impact of a Kids' Athletics program on the fundamental motor skills of fifth-grade primary school students. An experimental method utilizing a one-group pretest-posttest design was employed. The study involved 49 fifth-grade students (25 boys and 24 girls, aged 10–13 years) selected through purposive sampling. A modified Kids' Athletics program was implemented as an intervention over 16 sessions, with a frequency of 2–3 sessions per week. The Fundamental Sports Skills (FUS) test served as the research instrument; data analysis began with prerequisite testing (normality test), followed by the Wilcoxon Signed-Ranks test, as the data were not normally distributed. The results showed an improvement of 6.49 points. The Wilcoxon test yielded a significance value of p < 0.001, indicating a significant difference in fundamental motor skills before and after the intervention. In conclusion, the Kids' Athletics program is effective in enhancing the fundamental motor skills of primary school students, making it a viable alternative for Physical Education (PE) instruction in fostering the development of fundamental movement abilities.   Keywords: Basic Motor Skills; Kids' Athletics;  Primary School.